(Li, Na, K)OH hydration bonding thermodynamics : solution self-heating - Sun, Chang Qing (2019)
The resultant energy of solvent H–O bond exothermic elongation by O:⇔:O repulsion, featured at <3100 cm −1 , and the solute H–O bond endothermic contraction by bond-order-deficiency, at 3610 cm −1 , heats up the (Li, Na, K)OH solutions. The solution temperature increases linearly with the number fraction of the ordinary O:H–O bonds transiting into their hydration states. The elongated H–O bond emits >150% the O:H cohesive energy of 0.095 eV that caps the energy dissipating by molecular motion, thermal fluctuation, diffusion, and even evaporation. Therefore, the intramolecular H–O bond relaxation dictates the OH − solvation bonding thermodynamics and the performance of basic solutions.